Three-Dimensional Imaging and Gene Expression Analysis Upon Enzymatic Isolation of the Tongue Epithelium - Meisel, Christian T.; Pagella, Pierfrancesco; Porcheri, Cristina; Mitsiadis, Thimios A. (Frontiers in Physiology, 2020)
The tongue is a complex organ involved in a variety of functions such as mastication, speech and taste sensory function. Enzymatic digestion techniques have been developed to allow the dissociation of the epithelium from the connective tissue of the tongue. However, it is not clear if the integrity and three-dimensional architecture of the isolated epithelium is preserved, and, furthermore if this tissue separation technique excludes its contamination from the mesenchymal tissue. Here, we first describe in detail the methodology of tongue epithelium isolation, and thereafter we analysed the multicellular compartmentalization of the epithelium by three-dimensional fluorescent imaging and quantitative real-time PCR. Molecular characterization at both protein and transcript levels confirmed the exclusive expression of epithelial markers in the isolated epithelial compartment of the tongue. Confocal imaging analysis revealed that the integrity of the epithelium was not affected, even in the basal layer, where areas of active cell proliferations were detected. Therefore, the preservation of both the architecture and the molecular signature of the tongue epithelium upon enzymatic tissue separation enable further cellular, molecular and imaging studies on the physiology, pathology and regeneration of the tongue.